2020
DOI: 10.1136/bmjoq-2020-001035
|View full text |Cite
|
Sign up to set email alerts
|

Near Me at Home: codesigning the use of video consultations for outpatient appointments in patients’ homes

Abstract: Reforming the delivery of outpatient appointments (OPA) was high on the healthcare policy agenda prior to COVID-19. The current pandemic exacerbates the financial and associated resource limitations of OPA. Videoconsulting provides a safe method of real-time contact for some remotely residing patients with hospital-based clinicians. One factor in failing to move from introduction of service change to its general adoption may be lack of patient and public involvement. This project, based in the largest Island i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Contrary, a lack of both resources [22,25,42] and provider and staff knowledge surrounding updated patient flow protocols [15,22,25] serve as barriers to an enhanced throughput initiative. The review findings also suggest the implementation of additional telehealth initiatives [21,23,33], while also attributing this same identified construct as a barrier to the throughput initiative [19,22,42].…”
Section: Summary Of Evidencementioning
confidence: 88%
See 1 more Smart Citation
“…Contrary, a lack of both resources [22,25,42] and provider and staff knowledge surrounding updated patient flow protocols [15,22,25] serve as barriers to an enhanced throughput initiative. The review findings also suggest the implementation of additional telehealth initiatives [21,23,33], while also attributing this same identified construct as a barrier to the throughput initiative [19,22,42].…”
Section: Summary Of Evidencementioning
confidence: 88%
“…An ongoing initiative to maintain a high level of quality ambulatory/outpatient care continues to challenge the U.S. healthcare system as the COVID-19 pandemic continues. Evidence from this review suggests that enhanced safety and patient distancing protocols [20,27,41], in conjunction with appropriate provider training centered around such public health initiatives [19,23,31]. enhance outpatient providers' ability to increase patient throughput.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Previous research has also identified challenges building rapport during remote consultations (Verity et al, 2020) and identified that healthcare professionals are less likely to elicit additional concerns using this mode of communication (Hewitt et al, 2010). The sparse use of video consults may be considered surprising, as pre-pandemic there were extensive efforts to develop and subsequently adopt 'Attend Anywhere' (Wherton and Greenhalgh, 2020;Beattie et al, 2020), a video consultations platform which has national licence throughout Scotland. It is unclear why this technology was not adopted by pharmacy personnel in primary care despite its availability, and future work should explore patient and pharmacy personnel perceptions and preferences of remote consults in a post-COVID era (Murphy et al, 2021), which should inform evidenced-based guidelines on when, and how, to conduct remote consultations.…”
Section: Discussionmentioning
confidence: 99%
“…41 In the UK, a range of co-production policy and guidance, including the co-production model, have been developed (Case study 6). [42][43][44][45] Lesson 7: Ensure integration of care…”
Section: Case Study 3 Learning and Developing Preparedness Approaches From Periods Of Crisismentioning
confidence: 99%
“…The project led to 25 adaptations being made to the appointment process, as patients had the opportunity to design the healthcare delivery tool that best suited their needs. 43 Developing policy, guidance and tools towards co-production and patient, carer and community inclusion must be met with a commitment to the principles of co-production across the healthcare sector, and crucially by senior leadership. 44,45 Critically, patient, carer and community participation must be representative of the communities served.…”
Section: Case Study 6 Co-production In Scotlandmentioning
confidence: 99%